GPBAR1 is associated with asynchronous bone metastasis and poor prognosis of hepatocellular carcinoma - Chen, Nan; Wang, Jieqing; Zhou, Lei; Hu, Baiqiang; Chen, Yinzhong; Zhu, Zhuangchen (Frontiers in Oncology, 2023)
Background: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death in China. The asynchronous metastasis is a main reason of HCC recurrence, but current assessment of HCC metastasis and prognosis is far away from clinical satisfaction. Materials: In our study, we investigated the expression of GPBAR1 in HCC tissues and tumor-adjacent tissues by qRT-PCR and immunohistochemistry. The associations between GPBAR1 expression, clinicopathological factors and asynchronous metastases were assessed by the chi-square test. The overall survival curves of different variables were plotted with Kaplan-Meier method, and the statistical significance between different subgroups was analyzed with the log-rank test. The independent prognostic factors were identified by the Cox-regression hazard model. Results: GPBAR1 was highly expressed in HCC tissues than in tumor adjacent tissues. GPBAR1 expression in HCC was significantly higher than that in liver cirrhosis, followed by normal liver tissues. GPBAR1 was significantly associated with poor prognosis of HCC and can be regarded as an independent prognostic biomarker. Interestingly, GPBAR1 expression in HCC was substantially correlated with HCC asynchronous metastasis to bone but not to liver or lung. Conclusions: GPBAR1 was an independent unfavorable prognostic factor of HCC, and also an indicator of asynchronous bone metastasis but not liver or lung metastases. Our results could provide new aspect for HCC metastasis study and identify the high-risk HCC patients, which helps ameliorate the prognostic assessment of HCC.